2013
DOI: 10.1103/physrevstper.9.010118
|View full text |Cite
|
Sign up to set email alerts
|

Relativity concept inventory: Development, analysis, and results

Abstract: We report on a concept inventory for special relativity: the development process, data analysis methods, and results from an introductory relativity class. The Relativity Concept Inventory tests understanding of relativistic concepts. An unusual feature is confidence testing for each question. This can provide additional information; for example, high confidence correlated with incorrect answers suggests a misconception. A novel aspect of our data analysis is the use of Monte Carlo simulations to determine the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 36 publications
3
37
0
Order By: Relevance
“…First, we analyzed the students' overall performance on the test, finding that those at the median level had difficulty in correctly answering 6 of the items on the test. We also found that they had further difficulties with 7 of the 20 items (items 3,8,2,17,13,12,18). These items evaluate the geometric interpretation of dot product, the calculation of dot product of vectors written in the unit-vector notation, the graphic representation of unit vector, the calculation of direction of a vector written in unit-vector notation, the graphical subtraction of vector in 2D, the geometric interpretation of cross product, and the calculation of cross product magnitude as ABsinθ.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…First, we analyzed the students' overall performance on the test, finding that those at the median level had difficulty in correctly answering 6 of the items on the test. We also found that they had further difficulties with 7 of the 20 items (items 3,8,2,17,13,12,18). These items evaluate the geometric interpretation of dot product, the calculation of dot product of vectors written in the unit-vector notation, the graphic representation of unit vector, the calculation of direction of a vector written in unit-vector notation, the graphical subtraction of vector in 2D, the geometric interpretation of cross product, and the calculation of cross product magnitude as ABsinθ.…”
Section: Discussionmentioning
confidence: 60%
“…The second, that to some extent is a consequence of the first, concerns the availability of multiple-choice testing instruments. While several tests that incorporate the recommendations of physics education researchers [1][2][3] have been created [1,[4][5][6][7][8][9][10][11][12], one that evaluated students' understanding of vector concepts was not yet available. The third issue, suggested by the second, was the need for a large-population (or large sample) study at the university level that would analyze students' understanding of vector concepts after completing their introductory physics courses.…”
Section: Introductionmentioning
confidence: 99%
“…Two common perspectives on test development are Classical Test Theory (CTT) [32] and Item Response Theory (IRT) [33]. The majority of conceptual assessments in physics, at both the introductory and upper-division levels have been validated using CTT, while only a small number have been developed or analyzed using IRT [34][35][36][37]. One significant drawback of CTT is that all test statistics are population dependent.…”
Section: Validationmentioning
confidence: 99%
“…This is one example of what has necessitated the general classification for these instruments as CLAIs and not simply concept inventories. BEDCI [10] BCI [11] BRI [12] CCMI [13] CINS [14] CUE [15] DLCI [16] ECCI [17] ESICI [18] FTCI [19] GeDI [20] HPI-CI [21] LPCI [22] MCI [23] Meiosis [24] MWCS [25] NGCI [26] QMCA [28] QMCI [29] QMCS [30] R-FCI [31] RCI [32] ROXCI [33] SSCI [34] TUV [35] VKT [36]…”
Section: Differences In Instrument Designmentioning
confidence: 99%